2001
DOI: 10.1073/pnas.111158498
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the hydrophobic interaction by simulations of the aggregation of small hydrophobic solutes in water

Abstract: The hydrophobic interaction, the tendency for nonpolar molecules to aggregate in solution, is a major driving force in biology. In a direct approach to the physical basis of the hydrophobic effect, nanosecond molecular dynamics simulations were performed on increasing numbers of hydrocarbon solute molecules in waterfilled boxes of different sizes. The intermittent formation of solute clusters gives a free energy that is proportional to the loss in exposed molecular surface area with a constant of proportionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
171
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(191 citation statements)
references
References 28 publications
16
171
0
4
Order By: Relevance
“…The simulations of cluster formation yield a proportionality between transfer free energy and burial of nonpolar surface area that is similar to the one found from liquid-liquid transfer experiments [48]. The simulation results make the important point that a standard molecular force field is able to simulate the thermodynamics of hydrophobic free energy when a hydrophobic cluster is formed in water [48]. Rank and Baker [49] found that solvent-separated hydrocarbon clusters precede the desolvated clusters found in the interior of large hydrocarbon clusters.…”
Section: Simulation Of Hydrophobic Clusterssupporting
confidence: 54%
See 3 more Smart Citations
“…The simulations of cluster formation yield a proportionality between transfer free energy and burial of nonpolar surface area that is similar to the one found from liquid-liquid transfer experiments [48]. The simulation results make the important point that a standard molecular force field is able to simulate the thermodynamics of hydrophobic free energy when a hydrophobic cluster is formed in water [48]. Rank and Baker [49] found that solvent-separated hydrocarbon clusters precede the desolvated clusters found in the interior of large hydrocarbon clusters.…”
Section: Simulation Of Hydrophobic Clusterssupporting
confidence: 54%
“…The gain in negative free energy from adding a hydrocarbon molecule to a hydrocarbon cluster in water increases with the size of the cluster until limiting behavior is reached for large clusters. The simulations of cluster formation yield a proportionality between transfer free energy and burial of nonpolar surface area that is similar to the one found from liquid-liquid transfer experiments [48]. The simulation results make the important point that a standard molecular force field is able to simulate the thermodynamics of hydrophobic free energy when a hydrophobic cluster is formed in water [48].…”
Section: Simulation Of Hydrophobic Clusterssupporting
confidence: 51%
See 2 more Smart Citations
“…A connection between hydrophobic hydration and the pairwise hydrophobic interaction was found in 2001 by Raschke, Tsai and Levitt [40], who simulated the formation of contact clusters of hydrocarbon molecules in water and compared the results with the decrease in net ASA. When several hydrocarbon molecules are placed in a box of water molecules for a simulation study, the hydrocarbon contact clusters that are formed during simulation satisfy standard tests for being equilibrium clusters [40].…”
Section: Related Topicsmentioning
confidence: 99%